Determinant of Cash Holding in Indonesia - Widjanarko, Wirawan; Manurung, Adler Haymans; Machdar, Nera Marinda; Manurung, Gerry Juan Carlos; Hatibie, Ch. Indra W. P. (Journal of Ecohumanism, 2025)
This paper has objective to explore determinant of Cash Holding in Emerging Market. Variable is used to determine cash holding which is Gross Profit Margin, Accounts Receivable and Account Payable, Operational Cost, Exchange Rate and COVID-19. This paper used panel data Model to estimate relationship among variable. Research period is from 2016 to 2023 and 15 Companies. The results found that Gross Profit Margin, Accounts Receivable and Account Payable and COVID-19 significantly affect cash holding.